Impact of Crisis Management Practices on the Effectiveness of Crisis Management of Drones Threats in Dubai International Airport - Jasmi, Mohamad Ibrahim Hassan Mohamad Al; Udin, Mashitah binti Mohd; Siam, Mohammed R. A. (South Asian Journal of Social Sciences and Humanities, 2021)
The aim of the study is to examine the impact of the crisis management practices (readiness, crisis awareness, crisis control, crisis response) on effective crisis management in Dubai Airport. The study belongs to positivism philosophy, deduction approach, quantitative methodology, empirical survey passed study, used cross-sectional data, and data is original. The target or study population chosen for this research is the total number of employees, both senior and junior staff working at the Dubai international airport. The reason for this is that if crises stuck, all will be affected, and they have a big role to play in managing crises. The actual sample size is 364 employees, and the distributed survey is 440, which is distributed by using face-to-face data collection methods in a convenient technique of sample selection. Overall, direct relationships for the four predictors of crisis management are significant; The precedence for the relations based on the path coefficient value is crisis awareness (0.319), crisis control (0.107), crisis readiness (0.368), and crisis response (0.283). Replicating the study in other airports is recommended to have a better generalization.